Probiotics as Potential Enhancers of Veterinary Vaccines - Miriam Angulo; Carlos Angulo (Probiotics and Antimicrobial Proteins, 2026)

Immunological effects of β-glucan as a trained immunity-based adjuvant in vaccinated goats against anthrax - Miriam Angulo; Carlos Angulo (The Veterinary Journal, 2026)

Shifting alliances: exploring the impact of heat stress on soft coral microbiomes from different latitudes - Miriam Pascual-Benito; Paula De Castro-Fernández; Elisenda Ballesté; Carlos Angulo-Preckler; Pere Monràs-Riera; Conxita Avila; Cristina García-Aljaro (Frontiers in Marine Science, 2026)
Introduction Soft corals play key ecological roles in benthic communities by enhancing ecosystem health, providing structural complexity, cycling nutrients, and maintaining symbiotic relationships with diverse microbes. Although their microbiomes are highly structured and species-specific, little is known about their responses to extreme thermal anomalies such as marine heat waves. Methods We analyzed the microbiomes of three Malacalcyonaceans from polar ( Alcyonium haddoni ), temperate ( Alcyonium acaule ) and tropical ( Sinularia sp.) coastal environments, both in their natural habitats and after experimental heat exposure under controlled laboratory conditions. Using 16S rRNA amplicon sequencing, we assessed (a) bacterial taxonomic composition and structure along a latitudinal gradient and (b) the effects of thermal stress on these communities. Results Bacterial community composition differed among coral species and between corals and surrounding waters across all locations. The phylum Pseudomonadota dominated Alcyonium species and seawater samples from each environment. Alpha diversity generally increased under heat stress, though responses varied by species. Thermal stress altered bacterial communities, reducing the proportion of sequences matching natural-habitat microbiomes and making coral microbiota more similar to seawater communities. Host species and temperature treatment jointly explained 36.7% of the variation in microbial composition, highlighting a strong ecological pressure. Discussion Our findings demonstrate that rising seawater temperatures can profoundly disrupt coral–microbiota associations globally. The observed convergence of coral and seawater bacterial communities under heat stress suggests a loss of host-specific microbial signatures, potentially weakening coral resilience and affecting ecosystem functioning under future climate scenarios.

Probiotic potential and immunomodulatory effects of a thermophilic Bacillus sp. isolated from a hydrothermal vent - Miriam Angulo; Kevyn Guerra; Rafael Higuera; Eduardo López; Martha Reyes-Becerril; Elizabeth Monreal-Escalante; Carlos Angulo (Archives of Microbiology, 2026)

Enhancing the safety and shelf life of beef and plant-based burgers by combining High Hydrostatic Pressure (HHP) with nisin or a blueberry-derived product - Nikolaos Giannoulis; Theocharia Tsagkaropoulou; Carolina Bocigas Martin; Miriam Ortega-Heras; Mario González-Angulo; Beatriz Melero; Kimon Andreas G. Karatzas (Innovative Food Science & Emerging Technologies, 2026)

Plant- and microalgae-made fish vaccines - Carlos Angulo; Martha Reyes-Becerril; Bernardo Bañuelos-Hernández; Abel Ramos-Vega; Edgar Trujillo; Miriam Angulo; Alejandra Cisneros-Geraldo; Elizabeth Monreal-Escalante (Fish & Shellfish Immunology, 2025)

Immunometabolic effects of β-glucan-trained immunity in newborn goats - Miriam Angulo; Carlos Angulo (Research in Veterinary Science, 2025)

Probiotic Potential of Bacillus sp. 62A Isolated from a Marine Extreme Environment - Miriam Angulo; Kevyn Guerra; Paola Arevalo; Edgar Trujillo; Elizabeth Monreal-Escalante; Carlos Angulo (Probiotics and Antimicrobial Proteins, 2025)

Correction to: Potential assessment of probiotic Cystobasidium benthicum LR192 strain in mice - Miriam Angulo; Kevyn Guerra; Abel Ramos; Elizabeth Monreal-Escalante; Elizabeth Martínez; Carlos Angulo (Archives of Microbiology, 2023)

Potential assessment of probiotic Cystobasidium benthicum LR192 strain in mice - Miriam Angulo; Kevyn Guerra; Abel Ramos; Elizabeth Monreal-Escalante; Elizabeth Martínez; Carlos Angulo (Archives of Microbiology, 2022)

Developing oral nanovaccines for fish: a modern trend to fight infectious diseases - Carlos Angulo; Marlene Tello‐Olea; Martha Reyes‐Becerril; Elizabeth Monreal‐Escalante; Luis Hernández‐Adame; Miriam Angulo; José M. Mazon‐Suastegui (Reviews in Aquaculture, 2021)
Nanovaccines constitute an innovative approach in vaccinology, enabled by the nanotechnology advances on the synthesis, functionalization and application of nanoparticles for immunization. Currently, several organic materials such as chitosan, poly(lactic‐co‐glycolic acid), nanopoliplexes and virus‐like particles (VLPs) have been used for nanovaccine development to fight against fish diseases. The oral route is the most practical and economical for fish vaccination; thus, several oral vaccine candidates have been developed by using NPs in which the antigen is encapsulated, surface exposed or recombinantly ensembled (VLPs), leading to promising results in terms of protection capacity against infectious diseases. In this review, the state of the art on oral nanovaccine prototypes developed for use in fish was analysed and discussed. Oral nanovaccines have showed remarkably possibilities for application in fish aquaculture, which surely will be adopted by the industry in the following years.

Composition, antioxidant capacity, intestinal, and immunobiological effects of oregano (Lippia palmeri Watts) in goats: preliminary in vitro and in vivo studies - Martha Reyes-Becerril; Dante Gijón; Miriam Angulo; Juan Vázquez-Martínez; Mercedes G. López; Emmanuel Junco; Jose Armenta; Kevyn Guerra; Carlos Angulo (Tropical Animal Health and Production, 2021)

Immunostimulatory and antioxidant effects of supplemental feeding with macroalga Sargassum spp. on goat kids - Carlos Angulo; Luis Chavez-Infante; Martha Reyes-Becerril; Miriam Angulo; Reyna Romero-Geraldo; Ximena Llinas-Cervantes; Ramón Cepeda-Palacios (Tropical Animal Health and Production, 2020)